The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fimmu.2020.614697
|View full text |Cite
|
Sign up to set email alerts
|

The Systemic and Cellular Metabolic Phenotype of Infection and Immune Response to Listeria monocytogenes

Abstract: It is widely accepted that infection and immune response incur significant metabolic demands, yet the respective demands of specific immune responses to live pathogens have not been well delineated. It is also established that upon activation, metabolic pathways undergo shifts at the cellular level. However, most studies exploring these issues at the systemic or cellular level have utilized pathogen associated molecular patterns (PAMPs) that model sepsis, or model antigens at isolated time points. Thus, the dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The consequences of this change in diet also extended to systemic immune responses, as mice switched to FD could not efficiently clear systemic infections caused by Listeria monocytogenes , a known inducer of type I immune responses 22 (Fig. 1h–j ).…”
Section: Resultsmentioning
confidence: 99%
“…The consequences of this change in diet also extended to systemic immune responses, as mice switched to FD could not efficiently clear systemic infections caused by Listeria monocytogenes , a known inducer of type I immune responses 22 (Fig. 1h–j ).…”
Section: Resultsmentioning
confidence: 99%
“…In mice also lead to decrease of energy expenditure. 34,44 Active infection usually leads to the decrease of energetically expensive movement to make more energy available to the immune system. 45,46 However, caloric restriction has no significant effect on spontaneous physical activity in humans, [47][48][49] and fasting increases locomotor activity of rodents representing a higher exploratory behavior improving the chances to find food in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Fat metabolism is thought to play a role in cell function with specific lipid species either increasing or decreasing the inflammatory state of both myeloid and T cells (Hubler and Kennedy, 2016). In addition, mounting an immune response is thought to be energetically costly and adipose tissue wasting could be a mechanism for lipid mobilization to provide energy for the immune response (Eraud et al, 2005; Ganeshan et al, 2019; Johnson et al, 2021). We found that adipose tissue wasting had no influence on the induction of the immune response in the adipose tissue or spleen in response to a T. brucei infection.…”
Section: Discussionmentioning
confidence: 99%